Spinal dural arteriovenous fistula presenting as low back pain. Issue 4 (July 2019) - Chan, Kwok-Chun; Cheng, Fu-Jen; Hsu, Chih-Wei; Tsai, I-Ting; Chua, Choon-Bing; Chang, Chao-Sheng
Introduction: Low back pain or numbness of the lower extremities is quite common in the present population. Numerous conditions may cause these symptoms, including spinal vascular anomaly. Identifying and diagnosing the cause of these symptoms are crucial for treatment. Accurate diagnosis based on particular radiological findings in magnetic resonance imaging is crucial for administering adequate therapy to patients, especially in spinal dural arteriovenous fistula. Case presentation: We report a case presenting with low back pain and rapid deterioration in paraplegia. Magnetic resonance imaging provided the typical image presentations such as spinal cord edema with tortuous dilated perimedullary venous plexus. The patient was subsequently successfully treated with endovascular embolization. Discussion: Spinal dural arteriovenous fistula should be suspected in any patient who presents with myelopathy. Angiography remains the gold standard for confirmation of diagnosis. Conclusion: Prompt treatment with endovascular embolization or surgery could improve patients' outcomes.